Exploration of a potential advanced nursing practice role for adult critical care settings - Jamieson, Lynnette (2000)
"The purpose of the study was to explore issues which may support Australian critical care nurses to pre-determine the dimensions of a new advanced nursing practice role for adult critical care settings. This study was based on the qualitative approach of focus group methodology. Data was collected from a purposive sample of 26 critical care nurses working in regional Queensland. The data was subjected to thematic content analysis to inductively identify emerging themes." -- abstract.